Childhood maltreatment and transdiagnostic connectivity of the default-mode network: the importance of duration of exposure - Valencia, Noel; Seeger, Fabian R.; Seitz, Katja I.; Carius, Lisa; Nkrumah, Richard O.; Schmitz, Marius; Bertsch, Katja; Herpertz, Sabine (Journal of psychiatric research, 2024)
Childhood maltreatment (CM) has been demonstrated to be associated with changes in resting-state functional connectivity of the default-mode network (DMN) across various mental disorders. Growing evidence regarding severity of CM is available but transdiagnostic research considering the role of both severity and duration of CM for DMN connectivity at rest is still scarce. We recruited a sample of participants with varying levels of CM suffering from three disorders in which a history of CM is frequently found, namely, post-traumatic stress disorder, major depressive disorder, or somatic symptom disorder, as well as healthy volunteers to examine DMN connectivity in a transdiagnostic sample. We expected to find changes in inter-network connectivity of the DMN related to higher self-reported levels of CM severity and duration. Resting-state functional magnetic resonance imaging scans of 128 participants were analyzed focusing on regions of interest (ROI-to-ROI approach) and whole-brain Seed-to-Voxel analyses with retrospectively assessed CM as predictor in a regression model. Changes in connectivity between nodes of the DMN and the visual network were identified to be associated with CM duration but not severity. CM duration showed associations with increased connectivity of the precuneus and visual regions, as well as sensory-motor regions. The observed changes in connectivity could be interpreted as an impairment of information transfer between the transmodal DMN and unimodal visual and sensory-motor regions with impairment increasing with duration of exposure to CM.
Online verfügbar: 20. Juli 2024, Artikelversion: 20. Juli 2024
Gesehen am 22.10.2024